ECOBRICK DAN BIOKONVERSI: UPAYA MEMINIMALISASI SAMPAH DI PULAU BALANG CADDI - Fathinah Mardhatillah; Rahmawati Syam; Nana Wadaniah; Arina Fitrimasha; Muhammad Ilham; A Mukmin (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
The partners in this community service program are 13 young people on Balang Caddi Island who have dropped out of school and some of them do not have permanent jobs. Partners have problems with a lack of sources of income and their daily activities are disrupted by the large amount of rubbish on Balang Caddi Island. Balang Caddi Island is a small island located in Mattiro Bintang Village, Liukang Tupabbiring District, Pangkajene and Islands Regency. Problems experienced by partners can be minimized by involving them in waste management training using ecobrick and bioconversion techniques. Where, inorganic waste is used as ecobricks and organic waste is used as feed for Black Soldier Fly (BSF) maggots. The effectiveness of this program is measured using observation methods, interviews, as well as administering scales and tests. Program application includes several stages, namely program socialization, awareness raising, ecobrick training, BSF Maggot cultivation bioconversion training, ecobrick and bioconversion assistance and program evaluation. The aim of this community service is to improve partners' skills in managing waste so that it has economic value.